Role of the Built Environment in the Recovery From COVID-19: Evidence From a GIS-Based Natural Experiment on the City Blocks in Wuhan, China - Li, Maosu; Peng, Yi; Wu, Yijie; Xu, Jinying; Tan, Tan; Guo, Hui; Lu, Weisheng; Yeh, Anthony G. O.; Xue, Fan (Frontiers in Built Environment, 2022)
The built environment closely relates to the development of Covid-19 and post-disaster recovery. Nevertheless, few studies examine its impacts on the recovery stage and corresponding urban development strategies. This study examines the built environment’s role in Wuhan’s recovery at the city block level through a natural experiment. We first aggregated eight built environmental characteristics (BECs) of 192 city blocks from the perspectives of density, infrastructure supply, and socioeconomic environment; then the BECs were and associated with the recovery rates at the same city blocks, based on the public ‘Covid-19-free’ reports of about 7,100 communities over the recovery stages. The results showed that three BECs, i.e., ‘number of nearby designated hospitals,’ ‘green ratio,’ and ‘housing price’ had significant associations with Wuhan’s recovery when the strict control measures were implemented. At the first time of reporting, more significant associations were also found with ‘average building age,’ ‘neighborhood facility development level,’ and ‘facility management level.’ In contrast, no associations were found for ‘controlled residential land-use intensity’ and ‘plot ratio’ throughout the stages. The findings from Wuhan’s recovery pinpoint evidence with implications in future smart and resilient urban development. E.g., the accessibility of hospitals should be comprehensive in general; the average housing price of a city block can reflect its post-disaster recoverability compared to other blocks.